Missing Black males among preterm births in the US, 1995 to 2019. - Tim A Bruckner; Suman Chakrabarti; Brenda Bustos; Ralph Catalano; Alison Gemmill; Joan A Casey; Hedwig Lee (PLoS ONE)
Background In the US, non-Hispanic (NH) Black birthing persons show a two-fold greater risk of fetal death relative to NH white birthing persons. Since males more than females show a greater risk of fetal death, such loss in utero may affect the sex composition of live births born preterm (PTB; <37 weeks gestational age). We examine US birth data from 1995 to 2019 to determine whether the ratio of male to female preterm (i.e., PTB sex ratios) among NH Black births falls below that of NH whites and Hispanics. Methods We acquired data on all live births in the US from January 1995 to December 2019. We arrayed 63 million live births into 293 "conception cohort" months of which 2,475,928 NH Black, 5,746,953 NH white, and 2,511,450 Hispanic infants were PTB. We used linear regression methods to identify trend and seasonal patterns in PTB sex ratios. We also examined subgroup differences in PTB sex ratios (e.g., advanced maternal ages, twin gestations, and narrower gestational age ranges). Results The mean PTB sex ratio for NH Black births over the entire test period (1.06, 95% Confidence Interval [CI]: 1.05, 1.07) is much lower than that for NH white births (1.18, 95% CI: 1.17, 1.19). NH Black PTB sex ratios are especially low for twins and for births to mothers 35 years or older. Only NH white PTB sex ratios show a trend over the test period. Conclusions Analysis of over 10 million PTBs reveals a persistently low male PTB frequency among NH Black conception cohorts relative to NH white cohorts. Low PTB sex ratios among NH Black births concentrate among subgroups that show an elevated risk of fetal death. PTB sex ratios may serve as an indicator of racial/ethnic and subgroup differences in fetal death, especially among male gestations.